2009
DOI: 10.1136/jmg.2009.072900
|View full text |Cite
|
Sign up to set email alerts
|

Information for genetic management of mtDNA disease: sampling pathogenic mtDNA mutants in the human germline and in placenta

Abstract: Background Families with a child who died of severe, maternally inherited mitochondrial DNA (mtDNA) disease need information on recurrence risk. Estimating this risk is difficult because of (a) heteroplasmydthe coexistence of mutant and normal mtDNA in the same persondand (b) the so-called mitochondrial bottleneck, whereby the small number of mtDNAs that become the founders for the offspring cause variation in dose of mutant mtDNA. The timing of the bottleneck and of segregation of mtDNA during foetal life det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 43 publications
2
16
1
Order By: Relevance
“…A previous study on a placental fragment carrying m.3243A>G showed that a 60% mutant load was associated with a fivefold variation of the mtDNA copy number, but failed to establish a clear correlation between mutant load and mtDNA 11. In the current study, plotting the mutant load against the relative mtDNA amount for each of the five mtDNA mutations failed to detect any correlation, apart from m.3243A>G where the correlation was extremely strong (figure 2).…”
Section: Discussioncontrasting
confidence: 87%
“…A previous study on a placental fragment carrying m.3243A>G showed that a 60% mutant load was associated with a fivefold variation of the mtDNA copy number, but failed to establish a clear correlation between mutant load and mtDNA 11. In the current study, plotting the mutant load against the relative mtDNA amount for each of the five mtDNA mutations failed to detect any correlation, apart from m.3243A>G where the correlation was extremely strong (figure 2).…”
Section: Discussioncontrasting
confidence: 87%
“…However, in most asymptomatic siblings of an index patient (a low) mtDNA mutation load could not be excluded as they were not tested for the mutation on ethical grounds. Recurrence risk is increased in the case of gonadal mosaicism, which was shown for one of the de novo cases in the literature (case 9, table 2/case 58, online supplementary table S2 34 ). The single case where the mutation was present in subsequent pregnancies of the mother (case 12, table 2/case 59, online supplementary table S2 18 ) without being detectable in her blood or urine is presumably also an example of gonadal mosaicism.…”
Section: Recurrence Risk Of De Novo Mtdna Mutation or Diseasementioning
confidence: 53%
“…Statistical analysis of oocytes shows that in some cases the distribution of mutant mtDNA is consistent with random drift, but does not exclude the possibility of selection in the germline at an earlier stage [66]. On the other hand, a de novo mutation in a child and in oocytes appeared to be absent from the mother's other tissues [83], suggesting that it arose within the development of her germ cells. Comparison of human and mouse data suggests potentially important differences in both the type of rearrangement that is typical [59], [60] and in the bottleneck size [55].…”
Section: Mitochondrial Dna Bottlenecks In Human Germ Cell Developmentmentioning
confidence: 86%
“…The main drawback of CVS for mtDNA disorders is that it is not entirely certain that the level of mutant mtDNA detectable in a single CVS sample will accurately reflect that of the foetus [10]. Indeed, such data that exist suggest that there is a degree of variation of perhaps ±10% in the level of neutral [88] and pathogenic variants in placenta [83]. Moreover, certain centers are now offering PGD [5], [6], [23].…”
Section: Implications Of Heteroplasmy For Genetic Management Of Humanmentioning
confidence: 99%